Transcriptome Changes Associated with Boron Deficiency in Leaves of Two Citrus Scion-Rootstock Combinations - Liu, Xiao; Zhang, Jia-Wei; Guo, Ling-Xia; Liu, Yong-Zhong; Jin, Long-Fei; Hussain, Syed Bilal; Du, Wei; Deng, Zhao; Peng, Shu-Ang (Frontiers in Plant Science, 2017)
Boron (B) deficiency stress is frequently observed in citrus orchards and causes considerable loss of productivity and fruit quality. Carrizo citrange (Cc) has been reported as a rootstock more tolerant to B deficiency than Trifoliate orange (To). The ‘Newhall’ navel orange (Ns) performed better when grafted onto Cc (Ns/Cc) than when grafted onto To (Ns/To) under long-term B deficiency. The present study confirmed that Ns/Cc had higher boron content, leaf fresh weight, lower leaf chlorosis and stronger photosynthesis ability than Ns/To. Moreover, B-deficiency significantly reduced the chlorophyll and carotenoid content in Ns/To. The content of total soluble sugar and lignin were dramatically increased and the expression levels of photosynthesis-related genes were substantially down-regulated in Ns/To by B-deficient treatment. B-deficiency also strongly induced expression levels of chlorophyll decomposition-related genes, glucose synthesis-related genes and lignin synthesis-related genes, and significantly inhibited the expression of carotenoid synthesis-related genes in Ns/To. Overall, these findings indicated that the To had worse effect on the Ns than Cc via differently regulating these metabolic pathways under the long term of B-deficiency. The transcriptome analysis provided further information for understanding the mechanism of the different responses of scion-rootstock combinations to B-deficiency stress.